2016
DOI: 10.1053/j.gastro.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin Plus Albumin Is More Effective Than Albumin Alone in Improving Renal Function in Patients With Cirrhosis and Hepatorenal Syndrome Type 1

Abstract: Terlipressin plus albumin was associated with greater improvement in renal function vs albumin alone in patients with cirrhosis and HRS-1. Patients had similar rates of HRS reversal with terlipressin as they did with albumin. ClinicalTrials.gov no: NCT01143246.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
270
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(279 citation statements)
references
References 30 publications
3
270
3
3
Order By: Relevance
“…Details regarding the observed safety profiles for each individual study have been previously reported 16, 19. Overall, the incidence of adverse events was similar in the two treatment groups [terlipressin, 142/149 (95%); placebo, 137/150 (91%)], as was the incidence of serious adverse events [terlipressin, 96/149 (64%); placebo, 89/150 (59%)].…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Details regarding the observed safety profiles for each individual study have been previously reported 16, 19. Overall, the incidence of adverse events was similar in the two treatment groups [terlipressin, 142/149 (95%); placebo, 137/150 (91%)], as was the incidence of serious adverse events [terlipressin, 96/149 (64%); placebo, 89/150 (59%)].…”
Section: Resultsmentioning
confidence: 68%
“…Low patient numbers restricted prior studies in their ability to explore multiple predictive factors. Use of our larger pooled database, derived from individual patient data, demonstrates the value of such pooling to explore and identify previously unreported factors that may be important in predicting therapeutic response and survival in patients with HRS‐116, 19 and which require further study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations